A STUDY DESIGN REVIEW: OPHTHALMIC ARTERY DOPPLER IN PREECLAMPSIA STUDY - KAMILA, YURI; LEGIRAN, LEGIRAN (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2024)
Preeclampsia screening is a must for all pregnant women. Predicting preeclampsia using the ocular artery Doppler and comparing its efficacy to the uterine artery Doppler, which is now believed to be the most accurate tool in use, have both been the subjects of several studies. Depending on the research design, a number of investigations were conducted using various methods. The research proccess and, naturally, the findings will be impacted by the study design chosen. This study aims to review and evaluate the study designs of numerous recent studies on ocular artery Doppler in preeclamptic patients. It is a literature review that compiles articles from current English-language publications published in the years 2020 to 2023. The articles were found using the PubMed, Wiley, and BMJ search engines. Our findings show that the various study designs that were used had advantages and disadvantages. Future research ought to evaluate the advantages and disadvantages before selecting a study design.Keywords:  preeclampsia, ophthalmic artery Doppler, study design